Essays on Banking and Financial Regulations - Kravtsov, Oleg (2020)
This dissertation thesis comprises three working papers on the selected topics in financial regulations, supervision and financial stability. The focus is on the analysis of the response of financial institutions to the regulations and regulatory actions across the time and regions. The first essay examines the changes in the portfolio structures and investment decisions associated with EU-wide stress test rounds in 2011, 2014 and 2016. Using the empirical methods of causal inference and event study, we document a substantial impact of EU-wide stress tests in 2011, 2014 and 2016 on the banks’ portfolio strategies. We find that regulatory stress testing contributes to a decline of risk density of portfolios, which is mostly attributable to a decrease in its numerator i.e. risk-weighted assets. Seemingly it does not affect the realized risk that is measured by the proportion of non-performing exposure in portfolios. We argue that regulatory stress testing incentivizes banks to altering a mix of assets in their balance sheets towards less capital-intensive areas, potentially creating concerns on the concentrations and economic misallocation of resources. On the other hand, we observe that the enhanced regulatory scrutiny prevents the stress tested banks from engaging in risky behaviour i.e. increase risk in a portfolio or excessive loan growth. Thus, the regulatory stress testing fulfils its objective of promoting prudent risk management practices. Our results are robust in a number of alternative specifications such as modelling with instrument variable in the continuous form within the treated sample, under less restrictive assumptions of the structural equations and based on the alternative samples. In the second essay, we examine the impact of the supervision efforts as a monitoring activity and regulatory scrutiny on the risk-adjusted performance of the banking institutions in the Central Eastern Southern Eastern Europe.